Cdc42 promotes thyroid cancer cell proliferation and migration and tumor‐associated macrophage polarization through the PTEN/AKT pathway. Issue 8 (13th July 2022) - Huang, Deyi; Qiu, Huali; Miao, Lin; Guo, Lin; Zhang, Xiaoting; Lin, Mengmeng; Li, Zhongyun; Li, Fang
Abstract: The purpose of this study was to investigate the potential mechanism and function of Cdc42 in thyroid cancer. We found that knockdown of Cdc42 inhibited the migration and proliferation of WRO cells. This role of Cdc42 is achieved by interacting with PTEN and interfering with its PTEN nuclear translocation. The overexpression of Cdc42 enhances the production of lactic acid and promotes the polarization of M2 macrophages, and therefore M2 macrophages inhibit the function of T cells. Overall, Cdc42 can promote cell proliferation and migration through the PTEN/AKT pathway and promote tumor‐related M2 macrophage polarization and inhibit T cell activity by enhancing aerobic glycolysis, animal experiments confirmed that tumor volume increased after Cdc42 overexpressed in TBP‐3743 murine thyroid cancer cells. Increased infiltration of Treg and macrophages was also observed. taken together, our results indicate that Cdc42 can be used as a diagnostic and thyroid cancer Prognostic biomarkers and potential therapeutic targets.